Necessary travel : new area studies and Canada in comparative perspective - Hodgett, Susan, 1960-; James, Patrick, 1957- (Lexington Books, 2018)
This book explores New Area Studies in the twenty-first century. It addresses a blurring of genres between the social sciences and the humanities; expanding methodological innovation, reflective practice and co-production of knowledge with local people. It marks the significance of the local to the global in an increasingly complex world.